STRATEGI KOMUNIKASI PEMASARAN BATIK TULIS GIRILOYO DALAM MEMBANGUN BRAND AWARENESS - Sri Hastuti (2011)

(untitled)
Paguyuban Batik Tulis Giriloyo was founded in 2008, in accotiation Jogja Heritage Society with Australian Indonesian Partnership as NGO (Non Goverment Organization) to help Wukirsari society after earthquake in 2006. Paguyuban Batik Tulis Giriloyo have function to unite Batik artist and tool for promotion batik tulis Giriloyo, Batik from Wukirsari village, Imogiri, Bantul, Yogyakarta. The purpose from this researce is want to know Brand Awareness of Batik Tulis Giriloyo. Brand Awareness is ba